Autonome Systeme und Arbeit Perspektiven, Herausforderungen und Grenzen der Künstlichen Intelligenz in der Arbeitswelt - Hirsch-Kreinsen, Hartmut; Karacic, Anemari (Einzelveröffentlichungen Sozialwissenschaften, 2019)
Which new challenges, labor-political and ethical issues will the implementation of autonomous systems into the working world bring about? An interdisciplinary contribution to the debate.